Absence of detectable monkeypox virus DNA in 11, 000 English blood donations during the 2022 outbreak. Issue 4 (8th February 2023) - Knight, Chanice; Andreani, Julien; Garrett, Neil; Winter, Mark; Golubchik, Tanya; Breuer, Judy; Reynolds, Claire; Brailsford, Susan R.; Harvala, Heli; Simmonds, Peter
Abstract: Background: A large, worldwide outbreak of mpox (formerly referred to as monkeypox) involving mainly men who have sex with men commenced in May 2022. We evaluated the frequency of positivity for the causative agent, monkeypox virus (MPXV), in blood donations collected in August 2022, during the outbreak period in Southern England. Methods/Materials: The sensitivity and specificity of an MPXV‐specific PCR and a generic non‐variola orthopoxvirus (NVO) PCR were evaluated using samples from mpox cases and synthetic DNA standards. Residual minipools from nucleic acid testing were obtained from 10, 896 blood donors in Southern England, with 21% from London. Results: MPXV and NVO PCRs were both capable of detection of single copies of target sequence with calculated limits of detection (LOD)90  s of 2.3 and 2.1 DNA copies and analytical sample sensitivities of 46 and 42 MPXV DNA copies/ml, respectively. 454 minipools produced from 10, 896 unique donors were assayed for MPXV DNA by both methods. No positive minipools were detected by either PCR. Conclusions: Although blood donors are unrepresentative of the UK population in terms of MPXV infection risk, the uniformly negative MPXV DNA testing results provide reassurance that MPXV viraemia and potential transmission risk were rare or absent in donors during the outbreak period. Minipools from blood donors allow rapid implementation of large‐scale population‐based screening for emerging pathogens and represent an important resource for pandemic preparedness.